The role of constructivist theory and active learning in education (Journal of the College of Basic Education, 2022)
Its roots go back to the eighteenth century through the views of the Italian philosopher Gelosovkio, who indicated that humans can understand what they build by themselves, and there are many theorists who contributed to the crystallization of the idea of ​​​​constructivism, such as (King and Descartes) and the owner of the epistemological theory of evolution, Jean Piaget (Zaytoun, Kamal, 2003: 27 -28).